MEMBENTUK KARAKTER ANAK SEBAGAI GENERASI PENERUS BANGSA MELALUI PENDIDIKAN ANAK USIA DINI - I KETUT SUDARSANA (Purwadita : Jurnal Agama dan Budaya, 2017)
Early Childhood Education, which is one form of the provision of education with emphasis on  laying  the  foundation  toward  growth  and  physical  development  (coordination  of  fine  and gross  motor),  intellect  (the  intellect,  creativity,  emotional  intelligence,  spiritual  intelligence), socioemotional (attitude and behavior and religion), language, and communication, according to the uniqueness and the developmental stages through which early childhood. Therefore, the Early Childhood Education plays an important role in children's education. Through the Early Childhood Education, a child can be educated by teachers with clear methods and curriculum. Children can play and channeling energy through physical activity,  music, or hand skills.  But they  can also learn to  interact  in interpersonal  and intrapersonal. Children can gradually  be introduced letters or reading, the environment, agriculture and even industry. The introduction was not excessive, since the delivery tailored to the child's world, the world of play so that the learning  process  fun.  Children  are  often  expressing  ideas  and  feelings  through  play,  so  when children feel enjoyed and were happy with what was taught it, then by itself would be beneficial for their development.